A Further Survey of Multiple Authorship in the Astronomical Literature. (11th October 2017) - Smith, Graeme H.
Abstract: Authorship trends within the astronomical community have been studied using data drawn from the publication records of 12 refereed journals. The period covered by the study is 1991–2015. Across all journals, the annual fraction of papers with one or two authors has decreased with time, typically accompanied by an increased propensity for papers to have six or more co-authors. There is considerable variability in the behavior of three-to-five author papers. Reports on instrumentation developments within Publications of the Astronomical Society of the Pacific (PASP), a journal that places specific emphasis on publishing instrumentation papers, have a higher number of authors than average. The trends away from one-to-two author papers and toward papers with six or more authors show no correlation with either the annual number of papers per journal or the geographical diversity of the contributing author pools.